PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR IPAS KELAS IV SD - Intan Sari; Ulwan Syafrudin; Handoko; Fadhilah Khairani (STKIP Subang, 2026)
The problem in this study is the low learning outcomes of fourth-grade students of SD Negeri 1 Natar. The purpose of this study is to determine the significant effect of the use of problem-based learning models assisted by wordwall media on learning outcomes of science. This research method is a quasi-experimental. The research design used is a non-equivalent control group design. The study population was 110 students and the number of samples taken was 54 students, this sample was determined based on school considerations and recommendations and the learning outcomes of students of SD Negeri 1 Natar (purposive sampling). Data collection techniques were carried out using test and non-test techniques. The test used was the N-gain test and the hypothesis test of the simple linear regression test. The results of the N-Gain test showed that the experimental class that implemented the Problem Based Learning learning model assisted by wordwall media achieved an N-Gain score of 62.55% referring to the moderate level category (30% ≤ N-Gain < 70%). Then the results of the hypothesis test, namely the simple regression test, obtained the result 0.01 < 0.005, so H0 was rejected and Ha was accepted, namely Fcount > Ftable, meaning there was a significant influence of the use of the problem-based learning model assisted by wordwall media on the science learning outcomes of grade IV students of SD Negeri 1 Natar in the 2025/2026 academic year.